In-plane and out-plane bidirectional high-strength graphene heat conduction film as well as preparation method and application thereof
By vacuum impregnating epoxy resin into the graphene film to form a mortise and tenon structure, the problem of insufficient strength inside and outside the graphene film in the existing technology is solved, and the synergistic improvement of the high strength and high thermal conductivity of the graphene thermal conductive film is achieved.
Patent Information
- Application Number
- CN202511100348.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-07
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2045-08-07
AI Technical Summary
It is difficult with existing technologies to improve the in-plane and out-of-plane strength of graphene films without affecting the thermal conductivity of graphene, especially since the mechanical strength of the graphene films is severely weakened after high-temperature graphitization.
A small amount of epoxy resin is filled into the interior of the graphene membrane through a vacuum impregnation process. The mortise and tenon structure formed by the epoxy resin in the pores is used to improve the interlayer stress transfer efficiency and inhibit layer slippage, thereby improving the in-plane and out-of-plane strength of the graphene membrane.
The in-plane strength of the graphene thermal conductive film was increased to twice that of conventional films (63.3 MPa), and the out-of-plane strength was increased to six times (182.6 kPa), while the thermal conductivity coefficient remained at a high level of 1325 W/mK.
Smart Images

Figure CN120607878A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of graphene technology, and in particular to a graphene thermal conductive film with high strength in both in-plane and out-plane directions, and a preparation method and application thereof. Background Art
[0002] Graphene possesses the highest known tensile strength (130 GPa) and Young's modulus (1 TPa), as well as the highest carrier mobility (15,000 cm² / Vs) and thermal conductivity (5,000 W / mK). Since Professor AK Geim's team at the University of Manchester in 2004 successfully exfoliated graphene, the precise transfer of graphene's exceptional physical and chemical properties to its macroscopic assemblies has become a core research challenge worldwide.
[0003] Graphene membranes, the primary application form of nanoscale graphene, hold broad application prospects in fields such as optoelectronic sensing, lightweight aerospace, and thermal management of electronic devices. Their preparation primarily involves the macroscopic assembly of graphene oxide or graphene nanosheets followed by high-temperature graphitization. High-temperature graphitization (typically above 2800°C) helps repair defects in the graphene lattice, significantly improving the electrical and thermal conductivity of the membrane. However, after high-temperature graphitization, the mechanical strength of the graphene membrane is severely weakened, typically to around 20 MPa. This mechanical weakness stems from weak interlayer forces within the graphene and structural defects (such as wrinkles and pores) introduced during the post-high-temperature graphitization pressing process, severely restricting the widespread application of graphene membranes.
[0004] Currently, there are two main approaches to improving the mechanical strength of graphene membranes: First, strictly control the quality of the raw materials used for assembly, graphene oxide or graphene nanosheets. For example, by synthesizing ultra-large, low-defect-density graphene oxide to reduce edge defects, thereby increasing graphene crystallinity and enhancing the interlayer forces. Second, strictly control the assembly and pressing processes of graphene. For example, by using plastic stretching and pressure graphitization to reduce the generation of structural defects and thereby improve graphene crystallinity. However, while these methods improve the in-plane tensile strength, they may also significantly reduce the out-of-plane delamination strength, leading to delamination failure of the graphene membrane. Summary of the Invention
[0005] To address the difficulty in balancing in-plane and out-of-plane strength in existing technologies, the present invention provides a bidirectionally high-strength graphene thermally conductive film with both in-plane and out-of-plane properties, as well as its preparation method and application. A small amount of epoxy resin is filled into the graphene film through a vacuum impregnation process. The mortise-and-tenon structure formed within the pores by the epoxy resin improves interlaminar stress transfer efficiency and inhibits sheet slippage. This increases the in-plane strength to twice that of conventional films (63.3 MPa) and the out-of-plane strength to six times (182.6 kPa). Furthermore, due to the low proportion of epoxy resin and its discontinuous distribution, the thermal conductivity remains high at 1325 W / mK. This method, with readily available raw materials and a simple process, provides a viable path for the industrialization of graphene materials.
[0006] Specifically, the method includes the following steps: (1) A graphene film is prepared by applying pressure to the porous graphene material; the density of the graphene film is 1.65-1.85 g / cm 3 ; (2) preparing a modified bisphenol A epoxy resin-curing agent mixed solution; (3) vertically immersing the graphene film obtained in step (1) into the mixed solution obtained in step (2) until it is completely immersed, and obtaining a graphene / epoxy resin composite film by vacuum-assisted impregnation; (4) repeatedly washing the graphene / epoxy resin composite film obtained in step (3) with a heated anhydrous ethanol solution until no resin residue is left on its surface; (5) Pressurized thermal curing of the impregnated graphene membrane: The graphene membrane obtained in step (4) is placed in a flat-plate hot press, with the pressure controlled at 5-20 MPa, and initially cured at 50°C for 4 h, followed by secondary curing at 70°C for 8 h, to obtain a graphene thermal conductive membrane. The graphene with a porous structure forms wrinkles after the initial pressing process, and the resin injected under vacuum penetrates into the wrinkled area through the interlayer channels of the graphene, ultimately constructing a mortise and tenon-like structure.
[0007] Furthermore, the porous graphene material in step (1) includes but is not limited to open-pore materials such as graphene foam, graphene aerogel, and expanded graphite. The initial density of the porous graphene material is 0.1-0.2 g / cm 3 , with a thickness of 350-450 μm. Porous graphene material has good thermal conductivity.
[0008] Furthermore, the method of applying pressure in step (1) includes but is not limited to roller pressing and hot pressing. The direction of roller pressing is consistent with the horizontal direction of the porous graphene material. The final thickness of the graphene film can be controlled to be 25-30 μm and the density to be 1.65-1.85 g / cm by single or multiple roller pressing. 3 .
[0009] Furthermore, the mass ratio of the modified bisphenol A epoxy resin to the curing agent in the mixed solution of step (2) is 10:3. The mixed solution at this ratio exhibits good wettability to graphene. After the mixing is completed, the mixture is magnetically stirred at a rate of 200-500 rpm for a period of time, and then ultrasonic degassing is performed to remove residual bubbles in the mixed solution.
[0010] Furthermore, the vertical immersion in step (3) is to facilitate the escape of gas from the graphene membrane. The graphene membrane must be completely immersed in the mixed liquid. The vacuum-assisted impregnation is controlled at a vacuum level of 15-50 mbar, an impregnation temperature of 20-25°C, and an impregnation time of 0.5-5 hours. The temperature and vacuum level within these limits can prevent excessive resin infusion pressure from damaging the internal microstructure of the graphene membrane.
[0011] Furthermore, the temperature of the heated anhydrous ethanol solution in step (4) is controlled at 30-50° C. The heated anhydrous ethanol solution is intended to accelerate the dissolution of the epoxy resin and improve the cleaning efficiency. The criterion for determining whether there is no resin residue is to observe the surface of the graphene film through an optical microscope.
[0012] The present invention also provides a graphene thermal conductive film with high strength in both in-plane and out-plane directions prepared by the above method. The graphene thermal conductive film has a thickness of 22-27 μm and a density of 1.85-1.95 g / cm 3 The volume fraction of epoxy resin is 4-6%.
[0013] The present invention also provides the application of the above-mentioned bidirectional high-strength graphene thermal conductive film in high-strength and high-thermal-conductivity graphene materials, such as the preparation of laminated composite components for use as heat dissipation substrates for electronic devices.
[0014] The beneficial effects of the present invention lie in that by filling the structural defects generated during the pressing process of the graphene membrane with a small amount of epoxy resin, its in-plane and out-of-plane strength and thermal conductivity can be simultaneously improved (in-plane strength reaches 63.3 MPa, twice that of conventional graphene membranes; out-of-plane strength reaches 182.6 kPa, six times that of conventional graphene membranes; and thermal conductivity reaches 1325 W / mK). The epoxy resin forms a mortise-and-tenon-like connection structure within the pores of the graphene membrane, which not only improves the efficiency of interlaminar stress transfer but also dissipates a large amount of strain energy by inducing crack tip deflection, effectively inhibiting the slip of the graphene sheets and achieving a synergistic improvement in in-plane and out-of-plane strength. Furthermore, the low proportion of epoxy resin within the membrane and its discontinuous distribution preserve the original continuous thermal conductivity path of the graphene, ensuring that its excellent thermal conductivity is not affected. Furthermore, this method offers the advantages of readily available raw materials, simple processing, and low cost, which will help accelerate the industrialization of graphene materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 11 is the in-plane tensile mechanical curve of the graphene thermal conductive film obtained in Example 1 and Comparative Example 1; Figure 2 1 is the out-of-plane delamination mechanical curve of the graphene thermal conductive film obtained in Example 1 and Comparative Example 1; Figure 3 The scanning electron microscope images of the fracture surfaces of Example 1 and Comparative Example 1 after in-plane tensile fracture are shown, with a scale of 10 μm. Figure 4 This is a scanning electron microscope image of a typical dissipative structure during the in-plane stretching process of Example 1, with a scale of 1 micron. Figure 5 This is the mechanical enhancement mechanism of graphene thermal conductive film. DETAILED DESCRIPTION
[0016] The following examples are used to further illustrate the present invention. Their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all references are by weight and weight percentage.
[0017] Unless otherwise specified, the raw materials used in the present invention are conventional commercial products; the methods used in the present invention are conventional methods in the art unless otherwise specified.
[0018] The embodiments of the present invention are further described below with reference to a number of embodiments.
[0019] It should be clear that the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The singular forms "a", "an", "the" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise.
[0021] Example 1 (1) The initial density is 0.12 g / cm 3 , commercial graphene foam with a thickness of 450 μm was rolled in the same direction. The thickness was gradually reduced by 6 steps of rolling to obtain a final thickness of 30 μm and a density of 1.65 g / cm 3 , graphene film; (2) 3 parts by weight of a curing agent was dissolved in 10 parts by weight of a modified bisphenol A epoxy resin, stirred at room temperature for 5 minutes at a stirring rate of 400 rpm, and then degassed in an ultrasonic degassing apparatus for 5 minutes to obtain a modified bisphenol A epoxy resin-curing agent mixed solution; (3) The graphene film obtained in step (1) is completely immersed in the mixed solution obtained in step (2) vertically along the rolling surface, and then the whole is moved into a vacuum barrel, and vacuum impregnation is performed for 2 h under the conditions of setting the ambient temperature to 20 °C and a constant vacuum degree of 30 mbar to obtain a graphene / epoxy resin composite film; (4) Take out the graphene / epoxy resin composite film from the mixed solution and immerse it in anhydrous ethanol preheated to 50 °C. Gently shake the beaker for 1 min, then replace the anhydrous ethanol and repeat the cleaning three times. Use an optical microscope to confirm that there is no residual epoxy resin on the surface of the composite film to ensure complete cleaning.
[0022] (5) The cleaned composite film is placed in the middle of the platen of a flat hot press, with a polytetrafluoroethylene release cloth placed above and below. The pressure is set to 5 MPa, and the hot pressing temperature is maintained at 50 °C for 4 h for initial curing. The temperature is then raised to 70 °C and maintained for 8 h for secondary curing. After curing, the aforementioned graphene thermal conductive film is obtained.
[0023] (6) The thickness of the graphene thermal conductive film is 27 μm and the density is 1.95 g / cm 3 The epoxy resin volume fraction is 6%. Its in-plane strength is 63.3 MPa, out-of-plane strength is 182.6 kPa, and thermal conductivity is 1325 W / mK.
[0024] Example 2 (1) The initial density is 0.1 g / cm 3 , commercial graphene foam with a thickness of 350 μm was rolled in the same direction. The thickness was gradually reduced by 8 steps of rolling to obtain a final thickness of 28 μm and a density of 1.71 g / cm 3 , graphene film; (2) 3 parts by weight of the curing agent was dissolved in 10 parts by weight of the modified bisphenol A epoxy resin, stirred at room temperature for 5 minutes at a stirring rate of 300 rpm, and then degassed in an ultrasonic degassing apparatus for 5 minutes to obtain a modified bisphenol A epoxy resin-curing agent mixed solution; (3) The graphene film obtained in step (1) is completely immersed in the mixed solution obtained in step (2) vertically along the rolling surface, and then the whole is moved into a vacuum barrel, and vacuum impregnation is performed for 5 hours under the conditions of setting the ambient temperature to 20 °C and a constant vacuum degree of 15 mbar to obtain a graphene / epoxy resin composite film; (4) Take out the graphene / epoxy resin composite film from the mixed solution and immerse it in anhydrous ethanol preheated to 40 °C. Gently shake the beaker for 1 min, then replace the anhydrous ethanol and repeat the cleaning 4 times. Use an optical microscope to confirm that there is no residual epoxy resin on the surface of the composite film to ensure complete cleaning.
[0025] (5) The cleaned composite film is placed in the middle of the platen of a flat hot press, with a polytetrafluoroethylene release cloth placed above and below. The pressure is set to 15 MPa, and the hot pressing temperature is maintained at 50 °C for 4 hours for initial curing. The temperature is then raised to 70 °C and maintained for 8 hours for secondary curing. After curing, the aforementioned graphene thermal conductive film is obtained.
[0026] (6) The thickness of the graphene thermal conductive film is 26 μm and the density is 1.90 g / cm 3 The epoxy resin volume fraction is 5.31%. Its in-plane strength is 59.8 MPa, out-of-plane strength is 170.3 kPa, and thermal conductivity is 1332 W / mK.
[0027] Example 3 (1) The initial density is 0.2 g / cm 3 , commercial graphene foam with a thickness of 400 μm was rolled in the same direction. Its thickness was gradually reduced by 10 steps of rolling to obtain a final thickness of 25 μm and a density of 1.85 g / cm 3 graphene film; (2) 3 parts by weight of the curing agent was dissolved in 10 parts by weight of the modified bisphenol A epoxy resin, stirred at room temperature for 5 minutes at a stirring rate of 200 rpm, and then degassed in an ultrasonic degassing apparatus for 5 minutes to obtain a modified bisphenol A epoxy resin-curing agent mixed solution; (3) The graphene film obtained in step (1) is completely immersed in the mixed solution obtained in step (2) vertically along the rolling surface, and then the whole is moved into a vacuum barrel, and vacuum impregnation is performed for 0.5 h under the conditions of setting the ambient temperature to 25 °C and a constant vacuum degree of 50 mbar to obtain a graphene / epoxy resin composite film; (4) Take out the graphene / epoxy resin composite film from the mixed solution and immerse it in anhydrous ethanol preheated to 30 °C. Gently shake the beaker for 1 min, then replace the anhydrous ethanol and repeat the cleaning 5 times. Use an optical microscope to confirm that there is no residual epoxy resin on the surface of the composite film to ensure complete cleaning.
[0028] (5) The cleaned composite film is placed in the middle of the platen of a flat hot press, with a polytetrafluoroethylene release cloth placed above and below. The pressure is set to 20 MPa, and the hot pressing temperature is maintained at 50 °C for 4 hours for initial curing. The temperature is then raised to 70 °C and maintained for 8 hours for secondary curing. After curing, the aforementioned graphene thermal conductive film is obtained.
[0029] (6) The thickness of the graphene thermal conductive film is 22 μm and the density is 1.85 g / cm 3 The epoxy resin volume fraction is 4%. Its in-plane strength is 52.5 MPa, out-of-plane strength is 139.8 kPa, and thermal conductivity is 1345 W / mK.
[0030] Comparative Example 1 (1) The initial density is 0.11 g / cm 3 , commercial graphene foam with a thickness of 440 μm was rolled in the same direction. Its thickness was gradually reduced by 10 steps of rolling to obtain a final thickness of 24 μm and a density of 1.90 g / cm 3 graphene film; (2) This comparative example is a conventional graphene thermal conductive film without vacuum impregnation with epoxy resin; (3) The thickness of the graphene thermal conductive film is 24 μm and the density is 1.90 g / cm 3 The epoxy resin volume fraction is 0%. Its in-plane strength is 29.2 MPa, out-of-plane strength is 35.8 kPa, and thermal conductivity is 1398 W / mK.
[0031] The in-plane and out-plane mechanical curves of the graphene thermal conductive film sample are as follows: Figure 1 、 2 As shown in the figure, vacuum impregnation of epoxy resin significantly improved the in-plane tensile strength and out-of-plane delamination strength of the graphene thermal conductive film, reaching 63.3 MPa and 182.6 kPa, which are 2 times and 6 times that of conventional graphene films, respectively.
[0032] Scanning electron microscopy characterization showed that Figure 3 It is shown that vacuum impregnation of epoxy resin significantly improves the stress transfer efficiency between the graphene thermal conductive film layers, inducing crack tip deflection, which is manifested as a rough and rugged fracture surface accompanied by a large number of dissipative structures such as sheet pullout and shear bands. Figure 4 As shown in Figure 2, epoxy resin also provides a bridging effect to dissipate a large amount of strain energy and prevent the graphene sheets from sliding. Figure 5 As shown, these mechanisms give graphene thermal conductive film excellent in-plane and out-of-plane strength, laying a solid foundation for its wide application in multiple fields.
[0033] Comparative Example 2 The difference from Example 1 is that the graphene foam was not rolled but directly immersed in the epoxy resin solution. The resulting graphene film had poor thermal conductivity and significantly reduced strength. This is because the structure of the unrolled graphene foam was broken up when immersed in the epoxy resin solution, resulting in reduced thermal conductivity and strength.
[0034] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the scope of protection of the present invention.
Claims
1. A method for preparing a graphene thermally conductive film with high strength in both in-plane and out-plane directions, characterized in that: The following steps are involved: (1) Applying pressure to the porous graphene material to obtain a graphene membrane; the density of the graphene membrane is 1.65-1.85 g / cm 3 ; (2) preparing a modified bisphenol A epoxy resin-curing agent mixed solution; (3) vertically immersing the graphene film obtained in step (1) into the mixed solution obtained in step (2) until it is completely immersed, and vacuum-assisted impregnation is performed to obtain a graphene / epoxy resin composite film; in the vacuum-assisted impregnation, the vacuum degree is 15-50 mbar, the impregnation temperature is 20-25°C, and the impregnation time is 0.5-5 h; (4) repeatedly washing the graphene / epoxy resin composite film obtained in step (3) with a heated anhydrous ethanol solution until no resin residue remains on the surface; (5) Place the graphene film obtained in step (4) in a flat hot press, control the pressure at 5-20 MPa, perform preliminary curing at 50 °C for 4 h, and perform secondary curing at 70 °C for 8 h to obtain a graphene thermal conductive film.
2. The method according to claim 1, characterized in that The porous graphene material in step (1) is one of graphene foam, graphene aerogel, and expanded graphite; the density of the porous graphene material is 0.1-0.2 g / cm 3 , thickness is 350-450 μm.
3. The method according to claim 1, characterized in that The method of applying pressure in step (1) is one of roller pressing and hot pressing.
4. The method according to claim 1, wherein The mass ratio of the modified bisphenol A epoxy resin to the curing agent in the mixed solution of step (2) is 10:
3.
5. The method according to claim 1, wherein The temperature of the anhydrous ethanol solution in step (4) is 30-50°C.
6. A graphene thermally conductive film with high strength in both in-plane and out-plane directions prepared by the method according to claim 1, characterized in that: Thickness is 22-27 μm, density is 1.85-1.95 g / cm 3 ; The volume fraction of epoxy resin is 4-6%.
7. An application of the graphene thermal conductive film with high strength in both in-plane and out-plane directions as claimed in claim 6.
Citation Information
Patent Citations
Graphene heat conducting film and preparation method thereof
CN103805144A
Preparation method of graphene oxide / carbon nanotube reinforced glass fiber laminate
CN111073222A
Graphene film reinforced heat conduction composite film as well as preparation method and application thereof
CN112225929A
Preparation method of high-thermal-conductivity composite material
CN113999493A
Graphene film and graphene film enhanced heat conduction composite film
CN114381022A
Cited By
High-temperature paraffin impregnated graphite film for electrode and preparation method of high-temperature paraffin impregnated graphite film
CN121709430A